Hambatan Pelaksanaan SEMA No. 2 Tahun 2019 terhadap Pemenuhan Hak-hak Perempuan Pasca Cerai Gugat di Pengadilan Agama Kabupaten Kediri - Moch Ichwan Kurniawan; Nurul Hanani; Rezki Suci Qamaria (Al-Syakhsiyyah: Journal of Law & Family Studies, 2022)
SEMA No. 2 of 2019 which accommodates SEMA No. 3 of 2018 and PERMA No. 3 of 2017 concerning guidelines for adjudicating women's cases in conflict with the law makes new legal protection for women seeking justice, including for divorced wives. Where it allows a divorced wife to ask for her rights after the divorce is sued, namely iddah living and mut'ah income. This rule serves as a guide for judges under the Supreme Court including the Religious Courts of Kediri Regency, but in its implementation, it has not been in accordance with the purpose of the presence of these rules, the focus of this research is to explore the inhibiting factors for the implementation of SEMA No. The Religious Court of Kediri Regency and the solution given by the judge to the divorced wife due to the husband's fault. The results of this study show that the inhibiting factor is the absence of the divorced husband which causes the rules to not be implemented, the absence of instructions from the chairman of the court that requires applying SEMA No. 2 of 2019, and the lack of knowledge of divorced wives about the law. The solution is to present the husband in court so that it can be considered by the judge to decide the divorce case as possible, and the judge also tries to make husband and wife get back together in the household. Because the essence of the Religious Courts is a place to repair husband-wife relationships that experience cracks in the household.